The Influence of Perceived Country Origin of Green Products Towards Generation Z: Local vs. Global - Christiarini, Renny; Pratama, Desi; Putra, Edy Yulianto (Program MM Universitas Surabaya, 2024)
Purpose: This study aims to understand better the perception of the country of origin of green products towards the Generation Z population between local and global brands. This study also serves as a reference for future studies or research on how the influence of perception can determine the weight of how the Generation Z population views and potentially buy an environmentally friendly product between local and global brands. Method: This study uses primary data collected through questionnaires and distributed to the population of Generation Z from the island of Batam, with 376 valid respondents. Indicators from Partial Least Square-Structural Equation Modelling (PLS-SEM) were used to analyze how Local Brands and Global Brands can influence the perception of Green Products from the view of the Country of Origin from the Generation Z population. Result: The results of this study have practical implications, suggesting that the variables used in this study have a positive influence and are significant. For instance, Perceived Brand Globalness (PBG) and Perceived Brand Localness (PBL) have a positive and significant nature toward Brand Stereotype Warmth and Competence. Brand Stereotype Warmth and Competence also positively and significantly affect Perceived Value. Perceived Value also has a positive and significant nature towards Purchase Intentions. These findings are not only insightful but also relevant and applicable to the field of consumer behavior and green products.